Highly selective and stable bimetallic catalysts supported on different materials for n-butane dehydrogenation - Bocanegra, Sonia Alejandra (2009)
A study about the performance of Pt(0.3 wt%)Sn(0.3 wt%) catalysts supported on different materials in n-butane dehydrogenation is reported in this paper. The materials used as supports were γ-Al2O3, ZnAl2O4 spinel, MgAl2O4 spinel and spheres of α-Al2O3 with a washcoating of γ-Al2O3. The syntheses of both spinels leaded to very pure ZnAl2O4 and MgAl2O4 supports. The material prepared by washcoating showed the presence of an uniform and homogeneous layer of γ-Al2O3 (with a thickness between 12 and 18 μm) deposited on the spheres of α-Al2O3. The best behavior in activity, selectivity and stability through five severe cycles was achieved by bimetallic PtSn catalysts supported on MgAl2O4 spinel and on the material prepared by washcoating. The very good performance of these catalysts through the different cycles of reaction-regeneration can be due to the presence of metallic phases which preserve the strong intermetallic interaction along the different treatments, thus avoiding segregation processes.